Mature cystic teratoma arising from the fimbrial end of the left fallopian tube. a case report. Issue 2 (October 2020) - Chou, Szu-Yuan; Chen, Chi-Huang; Tzeng, Shang-Yu; Wen, Yu-Ching; Lin, Ming-Cheih; Tzeng, Chii-Ruey
We present a rare case of a woman with a mass containing soft tissue, fat, and calcified components attached to the fimbrial end of the left fallopian tube. A 38-year-old nulligravida woman who visited our clinic for infertility counseling had mild abdominal discomfort and a palpable mass in the lower abdomen. Multiple examinations were performed. Preoperatively, we considered that the patient had teratoma or teratocarcinoma of the left ovary. On exploratory laparotomy, we found that she had a mass with protuberances and a bulbous projection at one surface that was attached to the fimbrial end of the left fallopian tube. A histopathological examination showed a mature cystic teratoma that arose from the fimbrial end of the fallopian tube. Obstetricians should be aware of this abnormality. Early detection of this abnormality is advantageous for infertility counseling and planning of less invasive surgery in the hospital.